(untitled) (Research, Society and Development, 2021)
The use of alternative substrates, originating from organic residues, has been presented as an ecologically sustainable destination of solid residues, and its use in the production of seedlings has been the target of several researches in recent years, which aim to maximize the quality and field survival of individuals produced using these materials. Therefore, this work analyzed the seedling quality of Cojoba arborea var. angustifolia (Rusby) Barneby & J.W.Grimes in different substrates compositions. Eight treatments were adopted, with 15 repetitions each, and the following morphological parameters were analyzed: height (Alt), root length (CR), diameter at the height of the neck (DAC), dry mass of the aerial part (MSPA), dry mass of the root (MSR), total dry mass (MST), as well as the relationships: height by diameter the height of the neck (Alt/DAC), height by root length (Alt / CR), dry mass of the aerial part by dry mass of the root (MSPA/MSR), the Dickson Quality Index (IQD) and the number of nodules (QN). It was found that the treatments that contained chestnut shell in their composition, T2 and T4, showed higher biomass production. It was also noted that the use of vegetable ash, in addition to inhibiting nodulation, caused the death of almost 100% of the individuals in the treatment 8. It is also noteworthy that the commercial substrate (T1), only performed well in relation to the number of nodules. It is inferred that alternative substrates based on agroforestry residues, when used in correct proportions, provide high quality seedlings.